Bifunctional iminophosphorane superbase catalysed amide enolisation for enantioselective intramolecular reactions - Poh, YXC (2024)
Chapter 1 introduces the preparation of enantioenriched compounds, with increasing focus on enantioselective organocatalysis, Brønsted base/H-bond donor catalysis and enantioselective superbase organocatalysis. The history and development of various organocatalysts will be discussed, culminating in the discovery, development and applications of bifunctional iminophosphorane (BIMP) catalysts. Chapter 2 describes the development of a BIMP-catalysed enolisation of 2-arylacetyl and α-alkenyl amides for an enantioselective intramolecular Michael addition to tethered 2,5-cyclohexadienones. The substrate scope of this reaction, a preparative scale synthesis and further functionalisation of products formed will be detailed. Chapter 3 details our efforts in reacting 2-arylacetamide and ester pronucleophiles with various intramolecular sp2 and sp3 electrophiles through BIMP catalysis. Efforts to increase the Brønsted basicity of BIMP catalysts with the view towards facilitating reactions involving very high pKa pronucleophiles such as α-alkyl amides and esters will also be discussed.